CONCEPT-BASED INSTRUCTION: A THREE-STAGE TEACHING STRATEGY FOR THE ENGLISH-SPEAKING CLASS - Anis Firdatul Rochma (Universitas Wiralodra, 2023)
A mastery of English-speaking skills is a necessary ability for language learners. However, it is found that there is a treatment of oversimplifying talk found in the English learning materials, such as English textbooks, which creates a situation for the learners to fail in placing and applying the right expressions for a wider interaction in the real-life situation. It is vital for teachers to implement a teaching strategy to initiate an innovative English learning situation. Hence, this research suggests for the implementation of Concept-Based Instruction involving three stages, the orientation stage, execution stage, and control stage, within the English-speaking class. In specific, this research intends to (1) examine the implementation of CBI strategy to improve the speaking performance of language learners, and (2) identify the language learners’ perceptions towards the implementation of CBI strategy. The methods used in this paper were quantitative and qualitative designs involving the records of learners’ speaking performance as well as the researcher’s written notes. The results of the research reported that the CBI strategy can be considered a significant method to assist learners in obtaining the courage and confidence to actively engage in English-speaking activity.